The Institution-based View of Internationalization of Emerging Market Enterprises (EMEs): Research of Chinese Firms’ Outward FDI Based on Case-studies of Wanda Group’s Internationalization Strategy - HAN, LIPENG (2017)
This research examines the internationalization activities of emerging market enterprises (EMEs). Through systematically and critically analysing and evaluating one leg of international business strategy tripod (resource-based view, industry-based view, institution-based view), namely institution-based view especially, and the three pillars of institution-based view as well as the influence of three types of institutional pressures in detail, the research enables us to know the drivers, motivations, strategies and challenges of outward FDI from emerging markets especially Chinese private EMEs.